Peningkatan Profesional Mengajar Melalui Penerapan Supervisi Kelas pada Guru SMA Negeri 5 Aceh Barat Daya Tahun Pelajaran 2021/2022 - Cut Imilda Aryani (Universitas Syiah Kuala, 2022)
The application of classroom supervision can improve teacher professionalism in the learning process. The purpose of this research is to be able to find out the development of new theories about the application of classroom supervision in improving the teaching professionalism of teachers. SMA Negeri 5 Aceh Barat Daya. The subjects of this study were 30 teachers at SMA Negeri 5 Aceh Barat Daya. The research procedure is planning, taking action, observing and reflecting. The results of the research in the first cycle of the 1st meeting, the average score for collaboration ability is 2.1, the score for communication is 2, the value for innovation is 1.8, and the critical score is 1.2 for the percentage of completeness of 30 teachers reaching 33.33%. The 2nd meeting, the average value of the ability to collaborate 2.5, the value of communicating 2.4, the value of innovating 2.3, the critical value of 1.2. For the percentage of teaching professional completeness it reaches 60% completion. Cycle II of the 1st meeting, the average score for collaboration ability 2.9 score for communicating 2.7 score for innovation 2.5 critical score 1.6 For the percentage of professional teaching completeness the teachers achieved 73.33% completion. while the percentage value of the second cycle of the 1st meeting reached 73.33%, meaning the difference in the percentage value was 13.33%. The 2nd meeting assessed the average ability to collaborate 3.3 the value of communicating 3.6 to innovate 3.2 critical value 3.3 . The percentage value of completeness in professional teaching of teachers reached 83.33% completion.